Repatriation of international dual‐career couples - Kierner, Agnieszka; Suutari, Vesa (Wiley, 2017)
Combining the realities of dual-career couples (DCCs) and the requirements of international careers can be difficult. In order to improve the understanding of the repatriation experiences of international DCCs, we conducted interviews with both partners in 14 DCCs. Contrary to expectations, the majority of the interviewed couples reported very successful repatriation experiences and only a few adjustment challenges were raised. The interviews address the factors explaining such repatriation adjustment issues, and also elicit four key factors (active self-management of the expatriation process, earlier experience of expatriation and repatriation, the successful integration of work life and family life, and the realization of dual-career interests upon repatriation) connected with successful repatriation adjustment experiences.
Keywords: adjustment; dual-career couples; expatriation; repatriation; fi=Johtaminen ja organisaatiot|en=Management and Organization|